Risk Factors in Teenagers Offenders of the Juvenile Detention Center of El Tambo - Alberto Bueno, Yovana Luiza (2021)
Basic research of a descriptive nature, population of 50 teenagers who violate the intermediate program of the Juvenile Detention Center of El Tambo; the factors of social environmental risk in adolescents personally presented negative difficulties in attitudes and behaviors, low self-esteem, lack of values; in school, non-attendance at school, evasions, low grades, school repetition, conflicts with their teachers, failing to fulfill academic tasks, dropping out of school; in the family history of confined parents, having received physical and psychological punishments, evidencing situations of violence, lack of affectivity, moral and material abandonment. Conclusion personal, social and family factors.